2022
DOI: 10.1083/jcb.202105107
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensitive calcium flashes promote sustained RhoA activation during tight junction remodeling

Abstract: Epithelial cell–cell junctions remodel in response to mechanical stimuli to maintain barrier function. Previously, we found that local leaks in tight junctions (TJs) are rapidly repaired by local, transient RhoA activation, termed “Rho flares,” but how Rho flares are regulated is unknown. Here, we discovered that intracellular calcium flashes and junction elongation are early events in the Rho flare pathway. Both laser-induced and naturally occurring TJ breaks lead to local calcium flashes at the site of leaks… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 91 publications
1
51
0
Order By: Relevance
“…Rho flares in p115.S KD embryos displayed reduced intensity and duration of active RhoA at sites of TJ protein loss ( Figure 2 , A-C’, and Video 2 ). This reduction in active RhoA at flares led us to test whether downstream TJ repair is also compromised (Stephenson et al ., 2019; Varadarajan et al ., 2022). Indeed, the rapid junction contraction that immediately follows Rho flares in control embryos was absent in p115.S KD embryos ( Figure 2 , D-D’ ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rho flares in p115.S KD embryos displayed reduced intensity and duration of active RhoA at sites of TJ protein loss ( Figure 2 , A-C’, and Video 2 ). This reduction in active RhoA at flares led us to test whether downstream TJ repair is also compromised (Stephenson et al ., 2019; Varadarajan et al ., 2022). Indeed, the rapid junction contraction that immediately follows Rho flares in control embryos was absent in p115.S KD embryos ( Figure 2 , D-D’ ).…”
Section: Resultsmentioning
confidence: 99%
“…Rho flares rapidly repair the TJ barrier through localized actomyosin accumulation, which promotes junction contraction and TJ protein reinforcement (Stephenson et al ., 2019). Recent work revealed that intracellular calcium flashes, along with the mechanical stimulus of junction elongation, are early events in the Rho flare signaling pathway (Varadarajan et al ., 2022). These calcium flashes, mediated through mechanosensitive calcium channels, are required for sustained RhoA activation to support efficient repair and reinforcement of the TJ barrier (Varadarajan et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One open question is how compressive stress leads to increased recruitment of E-cadherin to promote cell-cell adhesion. Mechanical stimuli are known to remodel epithelial cell-cell junctions by junction elongation and contraction mediated via mechanosensitive channels (Varadarajan et al ., 2022). It is also well documented that adherens junctions become reinforced when cells are under tension (Borghi et al ., 2012; Charras and Yap, 2018; Pinheiro and Bellaíche, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…At sites of TJ breaches markers like ZO-1 disappear, and they reappear shortly after the recruitment of active RhoA ( Stephenson et al, 2019 ). This repair process is preceded by a local increase in the intracellular Ca 2+ concentration, suggesting that mechanosensitive Ca 2+ channels act as sensors of TJ breaches, and that a local increase in intracellular Ca 2+ activates RhoA at the TJs ( Varadarajan et al, 2022 ) ( Figure 5 ). These findings thus provide strong evidence that in reponse to local perturbations of TJ integrity, RhoA is recruited and/or activated locally to induce contractility of the actin cytoskeleton to support the repair of TJs and to re-establish the epithelial barrier function.…”
Section: Rho Family Small Gtpases In Membrane Polaritymentioning
confidence: 99%